2014
DOI: 10.1253/circj.cj-14-0064
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Contribution of Vascular Function to Baroreflex Regulation in Hypertension

Abstract: Background:We examined which pathophysiological abnormalities of vascular function might be closely associated with abnormal baroreflex regulation in subjects with hypertension. Methods and Results:In the cross-sectional assessment, 280 subjects with hypertension were enrolled for measurement of brachial-ankle pulse wave velocity (baPWV), radial augmentation index (rAI), flow-mediated vasodilatation (FMD) of the brachial artery and baroreceptor sensitivity (BRS). These parameters were measured again as prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…According to pulse wave velocity assessments in normotensive and hypertensive patients, atherosclerosis was significantly independently associated with reduced BRS. [28][29][30] Recently, we reported that the cardio-ankle vascular index, an indicator of arteriosclerosis, was independently associated with BRS. 31) In a carotid bulb containing highly concentrated baroreceptors, increased intima-media thickness was also reportedly associated with reduced BRS.…”
Section: Clinical Features Of Reduced Baroreflex Sensitivitymentioning
confidence: 99%
“…According to pulse wave velocity assessments in normotensive and hypertensive patients, atherosclerosis was significantly independently associated with reduced BRS. [28][29][30] Recently, we reported that the cardio-ankle vascular index, an indicator of arteriosclerosis, was independently associated with BRS. 31) In a carotid bulb containing highly concentrated baroreceptors, increased intima-media thickness was also reportedly associated with reduced BRS.…”
Section: Clinical Features Of Reduced Baroreflex Sensitivitymentioning
confidence: 99%
“…2-4 Attenuation of baroreflex sensitivity (BRS) in carotid atherosclerosis is likely to result from the reduced distensibility of carotid bulbs infiltrated by atherosclerosis. 5, 6 Also, it is possible that impaired BRS can accelerate atherosclerosis through inflammation and endothelial cell changes. 7, 8 Baroreflex and Cerebral Autoregulation of ABP was achieved using a servo-controlled finger plethysmograph (Finapres, Ohmeda, CO, USA for patients with carotid stenosis; and Nexfin, BMI for volunteers).…”
mentioning
confidence: 99%
“…36 This decrease augments BP fluctuations. Mancia et al reported that carotid arterial remodeling is associated with vvBPV abnormalities.…”
Section: Resultsmentioning
confidence: 95%